Implikacje kulturowe w badaniach marketingowych - wybrane zagadnienia - Sobocińska, Magdalena (Cultural Implications in Marketing Research - Selected Issues, 2006)
The influence of cultural conditions should be taken into account in marketing research during planning, realisation, as well as analyses and interpretation of results. The knowledge of cultural differences is important in shaping up relations and cooperation between a research institute and an employer of marketing research. The article presents the following issues: the examples of the impact of cultural conditions on the marketing research process, categories of equivalence of cross-cultural marketing research, research approaches: emic versus etic.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (2); 2006; nr 1110, s. 28-36